A proposed framework of supportive and palliative care for people with high-grade glioma. Issue 3 (27th July 2017) - Philip, Jennifer; Collins, Anna; Brand, Caroline; Sundararajan, Vijaya; Lethborg, Carrie; Gold, Michelle; Lau, Rosalind; Moore, Gaye; Murphy, Michael
Abstract: Background: Patients with malignant high-grade glioma (HGG) have significant supportive and palliative care needs, yet few tailored guidelines exist to inform practice. This study sought to develop an HGG framework of supportive and palliative care informed by needs reported by patients, families, and health care professionals (HCPs). Methods: This study integrates a mixed-methods research program involving: (i) exploring experiences through systematic literature review and qualitative study (10 patients, 23 carers, and 36 HCPs); and (ii) an epidemiological cohort study ( N = 1821) describing care of cases of HGG in Victoria, Australia using linked hospital datasets. Recommendations based on these studies were developed by a multidisciplinary advisory committee for a framework of supportive and palliative care based on the findings of (i) and (ii). Results: Key principles guiding framework development were that care: (i) aligns with patient/family caregiver needs according to illness transition points; (ii) involves continuous monitoring of patient/family caregiver needs; (iii) be proactive in response to anticipated concerns; (iv) includes routine bereavement support; and (v) involves appropriate partnership with patients/families. Framework components and resulting activities designed to address unmet needs were enacted at illness transition points and included coordination, repeated assessment, staged information provision according to the illness transition, proactive responses and referral systems, and specific regular inquiry of patients' and family caregivers' concerns. Conclusion: This evidence-based, collaborative framework of supportive and palliative care provides an approach for patients with HGG that is responsive, relevant, and sustainable. This conceptual framework requires evaluation in robust clinical trials.